Ultrasound-assisted extraction and the encapsulation of bioactive components for food applications - Mehta, Nitin; S, Jeyapriya; Kumar, Pavan; Verma, Akhilesh Kumar; Kaka, Ubedullah; Sazili, Awis Qurni (MDPI AG, 2022)
Various potential sources of bioactive components exist in nature which are fairly underutilized due to the lack of a scientific approach that can be sustainable as well as practically feasible. The recovery of bioactive compounds is a big challenge and its use in food industry to develop functional foods is a promising area of research. Various techniques are available for the extraction of these bioactives but due to their thermolabile nature, there is demand for nonthermal or green technologies which can lower the cost of operation and decrease operational time and energy consumption as compared to conventional methods. Ultrasound-assisted extraction (UAE) is gaining popularity due to its relative advantages over solvent extraction. Thereafter, ultrasonication as an encapsulating tool helps in protecting the core components against adverse food environmental conditions during processing and storage. The review mainly aims to discuss ultrasound technology, its applications, the fundamental principles of ultrasonic-assisted extraction and encapsulation, the parameters affecting them, and applications of ultrasound-assisted extraction and encapsulation in food systems. Additionally, future research areas are highlighted with an emphasis on the energy sustainability of the whole process.